"Can I hit that?" Vaping knowledge, attitudes and practices of college students. Issue 6 (24th August 2022) - Katz, Sherri Jean; Cohen, Elisia L.; Kinzer, Hannah T.
Abstract: Objective: Vaping rates among college students have been increasing significantly in recent years, due in large part to the diffusion of pod vaping devices (i.e., JUUL, Suorin) on American college campuses. In this study, we explore the ecological system of knowledge, attitudes, and practices in regards to this trend. Participants: Participants were 26 undergraduate students at the University of Minnesota. Method: Following a KAP (knowledge, attitudes, practices) approach, 8 focus groups were conducted in April/ May 2019. Results: Knowledge themes include awareness of the addictiveness of the devices and uncertainty regarding the health risks. Attitudinal themes include a dual perspective, wherein social use is acceptable, but everyday use is stigmatized. Practice themes included three evident stages: social connection, wherein the devices were used to achieve social advantage with peers; addiction, characterized by solitary, habitual use; and detachment, sometimes marked by a dramatic, public action filmed for social media. Conclusions: As we consider intervention points on college campuses, an understanding of knowledge, attitude, and practice themes can guide our approach. Recommendations for college vaping campaigns are discussed.